Base editing with high efficiency in allotetraploid oilseed rape by A3A‐PBE system. Issue 1 (4th August 2020) - Cheng, Hongtao; Hao, Mengyu; Ding, Bingli; Mei, Desheng; Wang, Wenxiang; Wang, Hui; Zhou, Rijin; Liu, Jia; Li, Chao; Hu, Qiong
Summary: CRISPR/Cas‐base editing is an emerging technology that could convert a nucleotide to another type at the target site. In this study, A3A‐PBE system consisting of human A3A cytidine deaminase fused with a Cas9 nickase and uracil glycosylase inhibitor was established and developed in allotetraploid Brassica napus . We designed three sgRNAs to target ALS, RGA and IAA7 genes, respectively. Base‐editing efficiency was demonstrated to be more than 20% for all the three target genes. Target sequencing results revealed that the editing window ranged from C1 to C10 of the PAM sequence. Base‐edited plants of ALS conferred high herbicide resistance, while base‐edited plants of RGA or IAA7 exhibited decreased plant height. All the base editing could be genetically inherited from T0 to T1 generation. Several Indel mutations were confirmed at the target sites for all the three sgRNAs. Furthermore, though no C to T substitution was detected at the most potential off‐target sites, large‐scale SNP variations were determined through whole‐genome sequencing between some base‐edited and wild‐type plants. These results revealed that A3A‐PBE base‐editing system could effectively convert C to T substitution with high‐editing efficiency and broadened editing window in oilseed rape. Mutants for ALS, IAA7 and RGA genes could be potentially applied to confer herbicide resistance for weed control or with better plant architecture suitable for mechanic harvesting.